Combatants of Muslim origin in European armies in the twentieth century far from jihad - Bougarel, Xavier; Branche, Raphaelle; Drieu, Cloe (Bloomsbury Academic, 2017)
During the two World Wars that marked the 20th century, hundreds of thousands of non-European combatants fought in the ranks of various European armies. This volume reintroduces the question of religious belonging and practice into the study of Muslim combatants in European armies in the 20th century, focusing on the combatants' viewpoint alongside that of the administrations and military hierarchy.